Work, labour, and professions in the Roman world - Verboven, Koenraad.; Laes, Christian. (Impact of Empire, 2016)
The economic success of the Roman Empire was unparalleled in the West until the early modern period. While favourable natural conditions, capital accumulation, technology and political stability all contributed to this, economic performance ultimately depended on the ability to mobilize, train and co-ordinate human work efforts. In Work, Labour, and Professions in the Roman World , the authors discuss new insights, ideas and interpretations on the role of labour and human resources in the Roman economy. They study the various ways in which work was mobilised and organised and how these processes were regulated. Work as a production factor, however, is not the exclusive focus of this volume. Throughout the chapters, the contributors also provide an analysis of work as a social and cultural phenomenon in Ancient Rome.